Call centres, quality of work life and HRM practices - Connell, Julia; Hannif, Z. (Emerald Group Publishing Limited, 2009)
Purpose – The paper seeks to determine whether and how the quality of working life (QWL) varies between call centres (CCs) in the in-house/outsourced, public and private sectors and the implications of these findings on human resource management (HRM). Design/methodology/approach – This paper reports on findings derived through empirical qualitative case study research in two Australian CCs: Govtcall, an in-house, public-sector CC, and Sales plus, an outsourced, private-sector CC. Quality of work life outcomes are determined through in-depth interviews with CSOs, supervisors and managers, where a comparative approach is utilised. Findings – The in-house, public-sector CC Govtcall emerges as being inferior in terms of job content, working hours and managerial/supervisory style and strategies. Conversely, Sales plus features a management model that is more akin to what would be expected in a CC operating under a professional service model. Research limitations/implications – The sample size was limited to two CCs; thus, the findings may not be representative of the wider CC context. Practical implications – A productivity orientation and employee focus are not a mutually exclusive phenomenon. Union presence and public-sector status do not guarantee better working conditions and higher QWL. Managerial styles and strategies have a significant impact on QWL in the CC context. Originality/value – QWL is an under-researched area where CCs are concerned. Similarly, much of the existing CC research is based on the private sector, despite the public sector emerging as a large user of CC operations.